INCOME AND EXPENDITURE ANALYSIS AND COPING MECHANISMS OF RICE FARMER HOUSEHOLDS IN MUARA BELIDA DISTRICT MUARA ENIM REGENCY BEFORE AND DURING THE PANDEMIC - Yunita; Riswani; Bidarti, Agustina (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
The pandemic has brought major changes to all aspects of the society, including social and economic changes. Various limitations are experienced by almost all levels of society. This study aims to 1) analyze changes in household income and expenditure of rice farmers before and during the pandemic and 2) describe the coping mechanisms of rice farmer households during the pandemic. The method used is a survey method. Data collection is done directly through interviews using a questionnaire. The samples used were 80 farmer households which were taken through simple random sampling technique. The data were processed quantitatively and explained descriptively, then presented in tabulated form and continued with paired-sample t test. The results show that 1) there is a significant decrease in household income, which is 5.65% during the pandemic compared to the income before the pandemic, 2) there is a shift (an increase of 1.88%) in household food consumption expenditures before and during the pandemic, while household non-food expenditure decreases by 3.65% during the pandemic, and 3) The survival strategies applied by farming households during the pandemic include a combination of active strategies and passive strategies by 62.5%, a combination of passive strategies and network strategies by 36% and those applying a combination of active strategies, passive strategies and network strategies by 15%. Farmer households are expected to be able to maximize the use of their yards, fish ponds, and livestock as an additional source of livelihood or an effort to reduce household non-food expenditure.